2013
DOI: 10.1007/s10826-013-9872-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic Hardship, Parent Positive Communication and Mental Health in Urban Adolescents Seeking Outpatient Psychiatric Care

Abstract: Economic hardship and poor parenting behaviors are associated with increased risk for mental health problems in community adolescents. However, less is known about the impact of socioeconomic status (SES) and parenting behaviors on youth at elevated risk for mental health problems, such as teens seeking outpatient psychiatric care. This study examined whether family SES and parent positive communication were directly and indirectly associated with mental health symptoms six months later in urban teens seeking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Our findings about family functioning perceived social support and resilience in poor Mexican youth [76] showed significant main effects of both, family functioning (F = 18.60; p < 0.01) and perceived social support (F = 11.71; p < 0.05) on resilience. In concordance with previous data [14,28,73,75], mother's level of education, father's occupation, adolescent's daily spending money, conflict family, and friend perceived social support were predictors of resilience by using logistic regression analyses.…”
Section: Family Functioning In Clinical and Nonclinical Adolescent Sesupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings about family functioning perceived social support and resilience in poor Mexican youth [76] showed significant main effects of both, family functioning (F = 18.60; p < 0.01) and perceived social support (F = 11.71; p < 0.05) on resilience. In concordance with previous data [14,28,73,75], mother's level of education, father's occupation, adolescent's daily spending money, conflict family, and friend perceived social support were predictors of resilience by using logistic regression analyses.…”
Section: Family Functioning In Clinical and Nonclinical Adolescent Sesupporting
confidence: 85%
“…Multiple regression analysis showed that the Rejection and Control of both parents were positive predictors whereas the Mother's Warmth predicted negatively: Internalizing (R 2 = 0.297; p = 0.035), Externalizing (R 2 = 0.275; p = 0.001) and Mixed Syndromes (R 2 = 0.289; p = 0.000). Preliminary conclusion suggests that negative parenting leads to negative outcomes as internalized problems, whereas positive parenting is a predictor of better psychological adjustment as has been reported previously [72][73][74][75].…”
Section: Family Functioning In Clinical and Nonclinical Adolescent Sesupporting
confidence: 67%
See 2 more Smart Citations
“…In line with the possibility that communication may facilitate or buffer intergenerational psychopathology risk, worse parent-adolescent communication has been associated with higher externalizing symptoms among urban youth seeking mental health services (Rodriguez, Nichols, Javdani, Emerson, & Donenberg, 2013). For African American mothers and adolescents, poor communication is associated with more youth depressive symptoms (Taylor & Seaton, 2008), and better communication predicts fewer youth problem behaviors (Smetana, Crean, & Daddis, 2002).…”
mentioning
confidence: 99%